2003
DOI: 10.1103/physrevb.68.224303
|View full text |Cite
|
Sign up to set email alerts
|

Atomic vibration amplitudes in fcc and hcp4Hethrough x-ray diffraction measurements

Abstract: Atomic vibration amplitudes in dense fcc and hcp 4 He crystals have been measured using synchrotron x rays from the dependence of integrated Bragg intensities up to wave vectors of 91 nm Ϫ1 . Observed raw Bragg x-ray integrated intensities cover an extraordinary range, greater than 10 5 , due to the combined effect of the Debye-Waller factor and electronic form factor. From analysis of these intensities mean-square atomic vibration amplitudes ͗u Q 2 ͘ and Lindemann ratios are determined. Path-integral Monte Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…For helium, in particular, this method has predicted kinetic-energy values [19] and Debye-Waller factors [31] in good agreement with data derived from experiments [32,33]. PIMC simulations have been also employed to study the isotopic shift in the helium melting curve [20,21].…”
Section: Introductionmentioning
confidence: 67%
“…For helium, in particular, this method has predicted kinetic-energy values [19] and Debye-Waller factors [31] in good agreement with data derived from experiments [32,33]. PIMC simulations have been also employed to study the isotopic shift in the helium melting curve [20,21].…”
Section: Introductionmentioning
confidence: 67%
“…To this end, the measured DebyeWaller factor must be recalculated. Experimental data for FCCP structures at low temperatures can be found in [10], and for BCC and FCC phases at comparatively high temperatures and pressures, they can be found in [4,11]. Results of calculations of the Lindeman parameter demonstrated that at low temperatures and relatively low pressures, values of the first-order correlation terms are comparable with those of the sixth-order anharmonisms.…”
mentioning
confidence: 77%
“…The reason is that high amplitudes of particle oscillations in these crystals gives rise to radically new effects observed in it [3,4]. In addition, these crystals are very promising for investigations of solid-liquid phase transitions [5].…”
mentioning
confidence: 99%
See 2 more Smart Citations